2014
DOI: 10.1007/s00233-014-9639-3
|View full text |Cite
|
Sign up to set email alerts
|

A family of varieties of pseudosemilattices

Abstract: In [3], a basis of identities {un ≈ vn | n ≥ 2} for the variety SPS of all strict pseudosemilattices was determined. Each one of these identities un ≈ vn has a peculiar 2-content Dn. In this paper we study the varieties of pseudosemilattices defined by sets of identities, all with 2-content the same Dn. We present here the family of all these varieties and show that each variety from this family is defined by a single identity also with 2-content Dn. This paper ends with the study of the inclusion relation bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It was shown that the classes of regular solid idempotent algebras and of pseudo-semilattices each form a variety [1,18]. The lattice of varieties of pseudo-semilattices was investigated extensively in [19]. The variety of bands is a subvariety of the variety of regular solid idempotent algebras; unlike the variety of all bands, the latter variety has a lattice of subvarieties that is of the power of the continuum (see the final remarks of [22, § 5]).…”
Section: Final Remarksmentioning
confidence: 99%
“…It was shown that the classes of regular solid idempotent algebras and of pseudo-semilattices each form a variety [1,18]. The lattice of varieties of pseudo-semilattices was investigated extensively in [19]. The variety of bands is a subvariety of the variety of regular solid idempotent algebras; unlike the variety of all bands, the latter variety has a lattice of subvarieties that is of the power of the continuum (see the final remarks of [22, § 5]).…”
Section: Final Remarksmentioning
confidence: 99%